Development of an effective composting process for oil palm industrial waste: optimization of process parameters - Mohammad, Noor; Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed (2011)
A batch study was carried out to optimize the parameters such as particle sizes (1, 2, 3, 5 mm), pH (4 to 7), mix ratio (1:1 to 1:3) of substrates (empty fruit bunch, EFB and palm oil mill effluent, POME) and supplementary nutrient (non food cassava starch) for an effective composting process. Total period of composting was considered to 35-40 days which is one of major focus of this study as composing process took longer time (>60 days) to make mature compost. In optimization, particle size of EFB with POME were found 2 mm that are the most suitable to grow microbes and degrade faster among other sizes. Substrate ratio 1:3 (EFB and POME) and pH 5.0 were found to be favorable for mature compost through faster degradation and microbial growth. Moreover, non-food cassava (NFC) used as supplementary nutrients for initial microbial growth (0 to 2%, w/w) was evaluated and found no significant variations in the findings.